2018
DOI: 10.1002/hep.29883
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic resection compared to chemoembolization in intermediate‐ to advanced‐stage hepatocellular carcinoma: A meta‐analysis of high‐quality studies

Abstract: This meta-analysis suggests that surgical resection provides survival benefits in patients with intermediate- to advanced-stage HCC. The evidence found herein may assist in the choice of treatment modality based on diverse definitions of operability. (Hepatology 2018).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
152
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 168 publications
(165 citation statements)
references
References 43 publications
13
152
0
Order By: Relevance
“…A small difference in size did not affect the procedures and curability of liver resection in many cases. A recent study indicated the survival benefit of liver resection in patients with IM-HCC, which included many large HCC > 5 cm in diameter with a small number [33]. A small increase in the number of tumors did not dramatically increase the risk or reduce the curability of RFA.…”
Section: Discussionmentioning
confidence: 99%
“…A small difference in size did not affect the procedures and curability of liver resection in many cases. A recent study indicated the survival benefit of liver resection in patients with IM-HCC, which included many large HCC > 5 cm in diameter with a small number [33]. A small increase in the number of tumors did not dramatically increase the risk or reduce the curability of RFA.…”
Section: Discussionmentioning
confidence: 99%
“…We have read the article of Hyun et al with great interest . We commend the authors for this study that tackles a crucial point in the treatment of hepatocellular carcinoma (HCC).…”
mentioning
confidence: 99%
“…The BCLC system recommends only transarterial chemoembolization (TACE) and sorafenib for intermediate and advanced HCC, yet several studies have suggested that expanding the selection criteria for hepatectomy can increase overall survival of these patients. Now, an elegant meta-analysis by Hyun and coworkers (4) suggests that, indeed, based on the evidence in 18 high-quality studies, hepatectomy can increase overall survival in patients with intermediate and advanced HCC.…”
Section: To the Editormentioning
confidence: 99%
“…In our analysis, three studies used a common database that had partially overlapping patients. (3)(4)(5) Therefore, theoretically, these patients should be investigated separately. However, those studies were performed in multiple centers with various inclusion criteria and enrollment periods, making it difficult to identify identical populations from the published data.…”
Section: Replymentioning
confidence: 99%
See 1 more Smart Citation